Label-free proteomic analysis reveals differentially expressed Wolbachia proteins in Tyrophagus putrescentiae: Mite allergens and markers reflecting population-related proteome differences - Erban, Tomas; Klimov, Pavel B; Harant, Karel; Talacko, Pavel; Nesvorna, Marta; Hubert, Jan (Journal of proteomics, 2021)
Tyrophagus putrescentiae is an astigmatid mite of great economic, medical and veterinary importance. The microbiome, especially intracellular bacteria, may affect allergy/allergen expression. We targeted Wolbachia proteins, allergen comparisons and markers in Wolbachia-mite interactions in three mite populations. A decoy database was constructed by proteogenomics using the T. putrescentiae draft genome, Wolbachia transcriptome assembly and current T. putrescentiae-related sequences in GenBank. Among thousands of mite-derived proteins, 18 Wolbachia proteins were reliably identified. We suggest that peroxiredoxin, bacterioferritin, ankyrin repeat domain-containing protein and DegQ family serine endoprotease indicate a higher-level bacterium-bacterium-host interaction. We produced evidence that the host-Wolbachia interaction is modulated through pattern recognition receptors (PRRs), mannose-binding lectins/mannose receptors, the cholinergic anti-inflammatory pathway with TNF-α, and others. We observed Tyr p 3 suppression in mites with Wolbachia, linking trypsin to PRR modulation. Nine out of the 12 current WHO/IUIS official allergens were reliably identified, but the remaining three allergens, Tyr p 1, 8 and 35, were detected as only trace hits. This study provides numerous markers for further Wolbachia-host interaction research. For accuracy, mite allergens should be considered according to abundance in species, but mite populations/strains, as well as their microbiome structure, may be key factors. SIGNIFICANCE: The astigmatid mites occurring in homes are significant producers of allergens that are highly dangerous to humans and domesticated animals. Mites are tightly associated with microorganisms that affect their biology and consequently allergy signatures. Mite populations were found to be infected with certain intracellular bacteria, but some populations lacked an intracellular bacterium. Our previous research showed that some populations of Tyrophagus putrescentiae are infected with Wolbachia, but some populations host additional bacteria of interest. Thus, there are not only interactions between the mites and Wolbachia but also likely an additional level of interaction that can be found in the interaction between different bacteria in the mites. These "higher-level" signatures and consequences that bacteria affect, including allergen production, are not understood in mites. In this study, we identified Wolbachia-specific proteins in mites for the first time. This study provides Wolbachia- and mite-derived markers that can be clues for describing "higher-level" mite-bacterium-bacterium interactions. Indeed, the microbiome contribution to allergies can potentially be derived directly from bacterial proteins, especially if they are abundant.
Keywords: Cholinesterase; Mites; Tyr p 3; proteom; Wolbachia; Peroxiredoxin; OmpA family protein; C-type lectin lectoxin-Lio1; roztoči; proteomika; Animals; Ankyrin repeat domain-containing protein; Allergens; zvířata; Proteomics; Pattern recognition receptors (PRRs); Bacterioferritin; Proteome; alergeny; DegQ family serine endoprotease